Pengaruh Budaya Kerja Dan Kondisi Kerja Terhadap Produktivitas Kerja Karyawan Arin Bakery - Young Parulian Panggabean; Imam Baidlowi; Toto Heru Dwihandoko (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This study aims to investigate the effect of work culture and working conditions on employee productivity at Arin Bakery. The sample of this study consisted of 30 employees from the total population. The sampling method used was saturated sample sampling technique, in which all members of the population were part of the research sample. Data were collected through a survey using a questionnaire that had been tested for validity and reliability. The questionnaire included questions related to work culture, working conditions, and work productivity. The collected data were then analyzed using regression analysis. The results showed that there is a positive and significant influence between work culture on employee productivity at Arin Bakery partially. This can be seen from the t-value (2.852) which is greater than the t-table (1.699) with a significance level of 0.008 which is smaller than 0.05, and a regression coefficient of 0.508. Furthermore, the results also show that there is a positive and significant influence between working conditions on employee productivity at Arin Bakery partially. It can be seen from the t-value (2.109) which is greater than the t-table (1.699) with a significance level of 0.000 which is also smaller than 0.05, as well as a regression coefficient value of 0.529. In addition, this study also shows that simultaneously, work culture and working conditions together have a significant influence on employee productivity at Arin Bakery. This can be seen from the results of the F test (74.176) which is greater than the F-table (8.169) with a significance level of 0.000 which is smaller than 0.05.